Learning from the Perspective of Parent and Teacher Creativity in Using Learning Media - Karliena, Yayuk; Guilin, Xie; Jiao, Deng; Wang, Yuanyuan; Zou, Guijiao (Al-Hijr: Journal of Adulearn World, 2024)
One of the impacts of the pandemic in the world of education is that the learning process must be carried out online. So efforts to provide learning media are too forced. Not only from an economic perspective, but also the ability to understand and use learning media. It takes creativity and solidarity between parents and teachers to outsmart and avoid bad things that will happen. The aim of this research is to determine the role of parents and determine teachers' strategies, designs and plans in determining learning media. This research uses qualitative methods using survey models and in-depth interviews. The results of this research are that parents and teachers have the same point of view and innovation in the use of learning media. This research confirms that the use of learning media is not only focused on learning objectives, but it is important to take into account several things: 1) how to select media, which consists of media selection models and reasons for using media. 2) media selection criteria consisting of the goals and objectives of media use, 3) media characteristics, 4) time and 5) cost of media use and 6) availability of the learning media. It is hoped that all steps chosen really take into account the principles of using learning media. Therefore, the limitation of this research is that researchers only focus on solution actions regarding innovation that make things easier for the parties involved in the learning process. It is hoped that future researchers can continue this research in certain subjects.